The Iemoto System in Japanese Performing Arts in Southern California Its Transformation and Influences on the Diaspora Musical Practices - Waseda, Minako (Asian Studies, 2008)
This study examines the transformation of the iemoto system as a cultural institution that has shaped traditional japanese music in southern California. The iemoto system is a hierarchical structure of teachers and students within a school of an art. The system prescribes specific processes for transmitting the art, as well as special teacher-student relationships within the structure. In southern California, the iemoto system has transformed itself to cope with Japanese-American environments. This transformation involved the weakening of ideological principles as the foundation of the iemoto system and produced features distinctive in southern California.